2011
DOI: 10.1080/10400419.2011.545721
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Experiences and Creativity in Fine Arts Students

Abstract: Studies on creative personality have revealed that the relationship between personality and creativity remains unclear, and various types of creative thinking have been have been associated with various personality traits. To assess the influence of dissociative experiences on creativity in the context of fine arts education, in which the creative process plays a key role, a sample of fine arts students received a test of creative potential and the dissociative experiences test. The results revealed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
3
13
0
1
Order By: Relevance
“…Moreover, many recognized experts continue to view dissociation solely as a manifestation of psychopathology (Ozer, Best, Lipsey, & Weiss, 2003). The results of the present study are, in contrast, consistent with the position of those who argue that dissociation occurs in nonpathological forms (Butler, 2006;Dalenberg & Paulson, 2009) or may even be health-positive (Chu, 2011;Perez-Fabello & Campos, 2011).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, many recognized experts continue to view dissociation solely as a manifestation of psychopathology (Ozer, Best, Lipsey, & Weiss, 2003). The results of the present study are, in contrast, consistent with the position of those who argue that dissociation occurs in nonpathological forms (Butler, 2006;Dalenberg & Paulson, 2009) or may even be health-positive (Chu, 2011;Perez-Fabello & Campos, 2011).…”
Section: Discussionsupporting
confidence: 68%
“…Hilgard (1986) proposed that, although dissociation can occur in response to trauma, it is also a normative phenomenon, seen to occur in situations as prosaic as driving or typing. Recent advances to this theory suggest that certain forms of dissociation may be nonpathological (Chu, 2011) and in some situations may even enhance effective functioning, particularly in regard to creativity (Perez-Fabello & Campos, 2011). Similarly, the phenomenon of health-positive effortless experiencing has been observed to be common in both creative and hypnotic states (Bowers, 1978).…”
mentioning
confidence: 97%
“…In fact, throughout the history of mediumship many mediums manifested talents that seemed to surpass their own expected abilities, like Hélène Smith (Flournoy, 1900), Pearl Curran (Prince, 1927), and Augustin Lesage (Victor, 1970). Even beyond direct mediumship research, other interesting studies have also described a significant and positive correlation between dissociation and artistic creativity (e.g., Domino, Short, Evans, & Romano, 2002;Pérez-Fabello & Campos, 2011), which seems to confirm Grosso's idea of a relationship between these two constructs. Braude (2002, p. 6) has defended that "dissociation can be a profoundly creativeindeed, continually creative activity", and he outlined many situations in which dissociation is used as a creative coping strategy against suffering and trauma (e.g., DID), but also in other non-pathological activities, as seen in certain creative hypnotic responses or behaviors and in cases of spontaneous emergence of latent abilities (e.g.…”
supporting
confidence: 62%
“…It has been proposed that non‐ordinary states of consciousness might help transcend constraints imposed by habitual, stereotyped ways of thinking and experiencing (Grosso, ). Recent studies have indeed found a significant association between measures of dissociation and creative capacity (Perez‐Fabello & Campos, ,b; Thomson, Keehn, & Gumpel, ; Van Heugten‐Van der Kloet et al., ) and dissociation and fantasy proneness (Giesbrecht, Merckelbach, & Geraerts, ).…”
mentioning
confidence: 94%